Pengaruh Profitabilitas, Likuiditas, dan Struktur Modal Terhadap Nilai Perusahaan (Pada Perusahaan Asuransi Yang Terdaftar di Bursa Efek Indonesia Tahun 2020-2023) - Renindy Indriany; Enny Arita (GLOBAL SCIENTS PUBLISHER, 2025)
The aim of this research is to examine the influence of Profitability, Liquidity and Capital Structure on company value. Where profitability is measured using the ROA ratio, liquidity is measured using the CR ratio, capital structure uses the DER ratio, and company value is measured using the PBV ratio. This research uses a sample of fifteen insurance companies listed on the Indonesia Stock Exchange in 2020-2023. The sample selection method uses purposive sampling. The data analysis method used in this research is multiple regression analysis. SPSS is used as a method for analyzing the data obtained. The results of this research show that the variables profitability and liquidity have a positive but not significant effect on company value. Meanwhile, the capital structure variable has a positive and significant effect on company value.